Andrographolide Inhibits Proliferation of Colon Cancer SW-480 Cells via Downregulating Notch Signaling Pathway - KHAN, IMRAN; Khan, Imran (My University, 2020)
Background: Recently Notch signaling pathway has gained attention as a potential therapeutic target for chemotherapeutic intervention. However, the efficacy of previously known Notch inhibitors in colon cancer is still unclear. The purpose of this study was to investigate the effect of andrographolide on aberrantly activated Notch signaling in SW-480 cells in vitro. Methods: The cytostatic potential of andrographolide on SW-480 cells was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay, morphology assessment and colony formation assay. The apoptotic activity was evaluated by FITC Annexin V assay, 4',6-diamidino-2-phenylindole (DAPI), Hoechst, Rhodamine 123 and Mito Tracker CMXRos staining. Scratch assay for migratory potential assessment. 7'-Dichlorodihydrofluorescein Diacetate (DCFH-DA) staining was used to evaluate the Reactive Oxygen Species (ROS) generation. Relative mRNA expression of Bax, Bcl2, NOTCH 1 and JAGGED 1 was estimated by Real-Time Quantitative Reverse Transcription PCR (qRT-PCR). Cell cycle phase distribution was evaluated Annexin V-FITC/PI staining. Results: MTT assay demonstrated dose and time dependent cytoxicity of andrographolide on SW-480 cells. It also inhibited the migratory and colony forming potential of SW-480 cells. Furthermore, andrographolide also showed disruption of mitochondrial membrane potential and induced apoptosis through nuclear condensation. Flow cytometric evaluation showed andrographolide enhanced early and late apoptotic cells and induced upregulation of proapoptotic (Bax and Bad) and downregulation of antiapoptotic Bcl2 in treated SW-480 cells. Andrographolide augmented intracellular ROS generation and induced G0/G1 phase cell cycle arrest in colon cancer SW480 cells. Furthermore, andrographolide repressed the Notch signaling by decreasing the expression of NOTCH 1 and JAGGED 1. Conclusion: Our findings suggested that andrographolide constraint the growth of SW-480 cells through the inhibition of Notch signaling pathway.
Keywords: Colon Cancer